Bergamot Leaf Extract as an Agent Against Chronic Liver Diseases? In Vitro and In Vivo Findings on Oxidative Stress Modulation - Vieira, Taynara Aparecida [UNESP]; Seloto, Danielle Gabriel [UNESP]; Rizzi, Joyce Santana [UNESP]; Peixoto, Paloma Vitória Lima [UNESP]; Corrêa, Giulia Vitória Betoni [UNESP]; Siqueira, Juliana Silva [UNESP]; Grandini, Nubia Alves [UNESP]; Nakandakare-Maia, Erika Tiemi [UNESP]; Valente, Letícia Cardoso [UNESP]; Francisqueti-Ferron, Fabiane Valentini [UNESP]; Ferron, Artur Junio Togneri; Baron, Giovanna; et al. (MDPI, 2025)
Oxidative stress is involved in pathophysiological mechanisms associated with a myriad of liver diseases. Bergamot (Citrus bergamia) leaves yield a high level of antioxidant polyphenolic compounds that may hinder the development of liver diseases, while their potential is yet to be fully explored. Thus, the aim of the study was to test the effects of bergamot leaf extract (BLE) on hepatic and mitochondrial oxidative stress in different models. In vivo study: Wistar rats were distributed into two groups: control diet (C) and high-sugar-fat diet (HSF) for twenty weeks. Afterward, the animals were redivided to initiate a ten-week treatment with BLE: C, HSF, and HSF+BLE. In vitro study: Rat hepatic mitochondria were isolated by differential centrifugation and used to assess safety and efficacy of the BLE. Hepatocyte monolayer and spheroids were applied to evaluate the safety of physiologically plausible BLE concentrations and their effects on hydrogen peroxide-induced cytotoxicity. The results showed that BLE improved metabolic parameters, reduced hepatic triglyceride levels, malondialdehyde, and increased catalase activity in vivo. In vitro, BLE decreased lipid peroxidation and increased the ratio of reduced and oxidized glutathione in chemically challenged mitochondria. BLE did not exert cytotoxicity in the hepatocyte monolayer and spheroids, while attenuated oxidative stress-induced cytotoxicity. Data indicate that in vivo and in vitro hepatic oxidative stress is modulated by BLE, reinforcing that BLE may act as an agent against chronic liver diseases.